2019
DOI: 10.1002/micr.30477
|View full text |Cite
|
Sign up to set email alerts
|

Association between operation‐ and operator‐related factors and surgical complications among patients undergoing free‐flap reconstruction for head and neck cancers: A propensity score‐matched study of 1,865 free‐flap reconstructions

Abstract: Objective: Efforts have been devoted to clarify the possible factors related to postoperative complications in free-flap reconstruction. While patient-related factors have been widely discussed, studies regarding the operation/operatorrelated factors are rather limited in the literature. This study was designed to investigate the relationship between operation/operator-related factors and the surgical complications in free-flap reconstruction following head and neck cancer resection. Methods: Data of 1,841 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(27 reference statements)
2
8
0
Order By: Relevance
“…One of the most‐often cited disadvantages of the SFF is prolonged operative time 2,8 . Several studies have described the association of increased operative time with surgical complications including flap failure as well as medical complications 13–15 . In this study, we found that when using the two‐team supine approach as described by Eskander et al, the SFF does not require significantly more time to complete 16 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…One of the most‐often cited disadvantages of the SFF is prolonged operative time 2,8 . Several studies have described the association of increased operative time with surgical complications including flap failure as well as medical complications 13–15 . In this study, we found that when using the two‐team supine approach as described by Eskander et al, the SFF does not require significantly more time to complete 16 .…”
Section: Discussionsupporting
confidence: 51%
“…2,8 Several studies have described the association of increased operative time with surgical complications including flap failure as well as medical complications. [13][14][15] In this study, we found that when using the two-team supine approach as described by Eskander et al, the SFF does not require significantly more time to complete. 16 We do acknowledge that this approach may be more difficult in obese patients and requires excellent team cooperation.…”
Section: Discussionmentioning
confidence: 80%
“…The use of vein grafts has been associated with significantly higher flap losses than those with direct microanastomosis 29 . Although the most common scenario in which vein grafting is required is the lack of nearby or even ipsilateral healthy recipient vessels, and such conditions were generally encountered in those who had a prior failed reconstruction, a repeated cancer resection, or those who already received radical neck dissection or radiotherapy 16 . However, in this study, there was no significant difference of vein graft use between those who had primary or recurrent cancers either before or after propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the surgery duration in our series was also significantly related to the risk of infection, with a median duration of 1 h and a half longer for the group suffering HAIs. Other authors have also demonstrated this relationship in patients with free-flap head and neck reconstruction [37,39]. These two findings-a high rate of free-flap failure and prolonged duration of surgery-should be areas for improvement.…”
Section: Risk Factors For Haismentioning
confidence: 74%